Current status of stem cell therapy, scaffolds for the treatment of diabetes mellitus. Issue 6 (November 2018) - Gharravi, Anneh Mohammad; Jafar, Alireza; Ebrahimi, Mehrdad; Mahmodi, Ahmad; Pourhashemi, Erfan; Haseli, Nasrin; Talaie, Niloofar; Hajiasgarli, Parinaz
Abstract: Diabetes mellitus (DM) remains the 7th leading cause of death in the world. Daily insulin injection is one component of a treatment plan for people with Diabetes mellitus type 1 (T1DM) that restores normal or near-normal blood sugar levels. However, Insulin treatment depends upon a variety of individual factors and leads to poor and drastic glycemic control. The need for an effective cell replacement strategy will be the aim of future clinical trials. Therefore, the aim of this systematic review is to outline the latest advances in scaffolding and stem cell therapy as a non-pharmacologic treatment for T1DM. It also emphasizes on some pancreas differentiation protocols and the clinical trials associated with stem cell therapy regarding T1DM in vitro and in vivo.